Happiness in world history - Stearns, Peter N., author.
1 online resource (vi, 226 pages)
Keywords: "Happiness in World History traces ideas and experiences of happiness from early stages in human history, to the maturation of agricultural societies and their religious and philosophical systems, to the changes and diversities in the approach to happiness in the modern societies that began to emerge in the 18th century. In this thorough overview, Peter N. Stearns explores the interaction between psychological and historical findings about happiness, the relationship between ideas and popular experience, and the opportunity to use historical analysis to assess strengths and weaknesses of dominant contemporary notions of happiness. Starting with the advent of agriculture, the book assesses major transitions in history for patterns in happiness, including the impact of the great religions, the unprecedented Enlightenment interest in secular happiness and cheerfulness, and industrialization and imperialism. The final, contemporary section covers fascist and communist efforts to define alternatives to Western ideas of happiness, the increasing connections with consumerism, and growing global interests in defining and promoting well-being. Touching on the experiences in the major regions of Asia, Africa, Latin America, Europe, and North America, the text offers an expansive introduction to a new field of study. This book will be of interest to students of world history and the history of emotions"--